Learning path : issues and next steps in software architecture. - Schutta, Nathaniel T.; Newman, Sam; Ford, Neal; Richards, Mark; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2016)
"You've got the basic principles of software architecture down, but now you're looking for strategic ways of dealing with today's demands while planning for the future. With this Learning Path you'll acquire crucial soft skills, such as communication and modeling, and get a deeper understanding of service-based architectures including an in-depth look into microservices. With these skills in your deck, you'll be confident in your ability to handle the toughest challenges that come your way."--Resource description page.
I'm a software architect, now what? : leadership, relationships, and communication / Nathaniel Schutta -- Modeling for software architects : from conceptual to deployment diagrams and data models to review processes / Nathaniel Schutta -- The principles of microservices : embrace autonomy to optimize performance / Sam Newman -- Service-based architectures : structure, engineering practices, and migration / Neal Ford and Mark Richards.
Presenters, Nathaniel Schutta, Sam Newman, Neal Ford and Mark Richards.
Title and publication information from resource description page (Safari, viewed May 4, 2016).
Keywords: Software architecture; Electronic data processing -- Distributed processing; Electronic books